Chicken run - Lord, Peter; Lord, Peter (USA : Dreamworks Home Entertainment [production company] ; Kuala Lumpur : Berjaya HVN Sdn. Bhd. [distributor], 2000)
Chicken run is the year's most original comedy hailed by critics and audiences alike as'magical entertainment for all ages!'
Executive producer, Jake Eberts, Jeffrey Katzenberg, Michael Rose ; editor, Mark Soldman ; screenplay, Karey Kirkpatrick
VCD format
Keywords: Animated films; Comedy films; Animal in motion pictures